2013
DOI: 10.1177/0163443712467594
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeping Twitter: message diffusion in political hashtags

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 14 publications
3
85
1
14
Order By: Relevance
“…These hashtags were popular among prolific users, particularly those tweeting hashtags associated with the Occupy movement, Kony2012, and the Spanish Indignados protests, a first pointer to their character as transnationally followed events. Bastos et al (2013b) also reported that message replication with protest hashtags was not correlated with network topology, with retweets cascading mostly from users with an average following that posted protest hashtags profusely. Instead of depending on user-hubs acting as gatekeepers, message cascades were associated with the intense activity of individuals with relatively few connections.…”
Section: Introductionmentioning
confidence: 99%
“…These hashtags were popular among prolific users, particularly those tweeting hashtags associated with the Occupy movement, Kony2012, and the Spanish Indignados protests, a first pointer to their character as transnationally followed events. Bastos et al (2013b) also reported that message replication with protest hashtags was not correlated with network topology, with retweets cascading mostly from users with an average following that posted protest hashtags profusely. Instead of depending on user-hubs acting as gatekeepers, message cascades were associated with the intense activity of individuals with relatively few connections.…”
Section: Introductionmentioning
confidence: 99%
“…Parece que en ambos contextos enlazan por imitación, en el sentido de copiar los mismos titulares que proponen los medios, sin seguir ninguna estrategia. Esta realidad se aleja de las investigaciones que sostienen que los usuarios adoptan funciones similares a las del periodista gatekeeper (Bastos et al, 2013;Shoemaker & Vos, 2009), y que contribuyen a evaluar los asuntos de interés (Bruns, 2005;Bruns & Burgess, 2012).…”
Section: Conclusiones Y Discusiónunclassified
“…Para ello, se abordan dos casos de actualidad relevantes en España, #ArdeValencia (incendios forestales de Valencia) y #25N (elecciones al Parlamento de Cataluña), concretamente para analizar los links incorporados junto a los dos hashtags. Se trata de estudiar los mensajes enlazados, establecer las pautas de comportamiento de cada tipo de actor y evaluar si los ciudadanos asumen las funciones del periodista gatekeeper cuando enlazan contenidos, es decir, si seleccionan y jerarquizan contenidos en función de sus seguidores, y si refuerzan o contrarrestan la agenda mediática (Bastos, Raimundo & Travitzki, 2013;Shoemaker & Vos, 2009). También se revisan las fuentes de los enlaces, para verificar si predominan las convencionales y si se introduce a nuevos actores.…”
Section: Introductionunclassified
“…Much has been written about the news potential of blogs and microblogs (see for example Siles, 2011;Papacharissi and Oliveira, 2012;Bastos et al, 2013), as well as about the political potential of online space in general (e.g., Bohman, 2004;DeLuca and Peeples, 2002;Downey and Fenton, 2003). In fact, since the dawn of the Internet age, discussion of the democratic potential of Internet-mediated space has been one of the major top level conversations.…”
Section: Fcj-194 From #Racefail To #Fergusonmentioning
confidence: 99%